Impact of the right issue during pandemic: evidence from indonesia stock exchange - Tona Aurora Lubis; Firmansyah Firmansyah; Novita Sari; Maryati Ningsih (INOVASI, 2022)
This study has been carried out to identify the impact of right issues announcement during the Covid pandemic in Indonesia Stock Exchange. In this article, we use an event study approach to empirically study the trading frequency, actual return, stock return and trading volume activity on response due to right issues announcement. This article used window's method with 3 days, 7 days, and 10 days period.The main conclusion from this finding is that during the covid pandemic there are differences in the actual average return and the average stock return in a period of 3 days, 7 days and 10 days both before and after the issuance of right issues. Likewise, the average trading frequency, during the covid pandemic, there was a difference in the average trading frequency in the 3 day and 7 day periods before and after the issuance of the right issue. An interesting conclusion from this finding is that the issuance of right issues during the covid pandemic will increase the actual average return and average stock return in the period of 3 days, 7 days and 10 days after the issuance of the right issues. However, the trading frequency only increased in the period of 3 days and 7 days after issuance and then decreased after 10 days of the issuance of the right issue itself. Meanwhile, this finding also shows that there is no difference in trading volume activity both before and after the issuance of right issues.